2015
DOI: 10.1016/s2352-3026(14)00035-0
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic score for acute graft-versus-host disease based on biomarkers: a multicentre study

Abstract: SUMMARY Background Graft-versus-host disease (GVHD) is the major cause of non-relapse mortality (NRM) after allogeneic hematopoietic stem-cell transplantation (HCT). The severity of symptoms at the onset of GVHD does not accurately define risk, and thus most patients are treated alike with high dose systemic corticosteroids. We aimed to define clinically meaningful risk strata for patients with newly diagnosed acute GVHD using plasma biomarkers. Methods We prospectively collected plasma from 492 HCT patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
199
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(210 citation statements)
references
References 38 publications
8
199
0
3
Order By: Relevance
“…1 Although the overall frequency of GVHD has remained stable during the past decade, its presentation has shifted toward gastrointestinal involvement as the major cause of morbidity and away from severe damage to the skin and liver. 1,2 The result of these clinical trends has been a reduction in the frequency of grade 3-4 GVHD to ,10% in most centers, along with a 50% reduction in nonrelapse mortality (NRM). 1 Retrospective analyses demonstrate that patients with more severe peak symptoms and especially more prolonged acute GVHD have substantially higher mortality rates than those with less severe and shorter-duration GVHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although the overall frequency of GVHD has remained stable during the past decade, its presentation has shifted toward gastrointestinal involvement as the major cause of morbidity and away from severe damage to the skin and liver. 1,2 The result of these clinical trends has been a reduction in the frequency of grade 3-4 GVHD to ,10% in most centers, along with a 50% reduction in nonrelapse mortality (NRM). 1 Retrospective analyses demonstrate that patients with more severe peak symptoms and especially more prolonged acute GVHD have substantially higher mortality rates than those with less severe and shorter-duration GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 If it were possible to predict the ultimate severity of GVHD before or at the onset of symptoms, preemptive immune suppressive therapy could be administered in an effort to blunt the intensity of tissue damage, especially in the gastrointestinal tract. 2,7 Research on the predictive value of plasma biomarkers has yielded several candidate analytes that have been measured at higher levels in patients with GVHD than in allografted controls with no GVHD or less severe GVHD. 2,[7][8][9][10][11][12][13] In the study reported here, 2 cohorts of patients provided frequent blood samples after allogeneic transplantation, and we measured plasma levels of 23 analytes previously reported to be elevated in patients with GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…The Ann Arbor grade is based upon serum or plasma levels of TNF receptor-1 (TNFR1), regenerating islet-derived 3-alpha (REG3α) and suppression of tumorigenicity 2 (ST2), and has been validated from independent cohorts of patients with aGVHD from the University of Michigan, the University of Regensberg and from multicenter Blood and Marrow Transplant Clinical Trials Network aGVHD treatment trials 0302 and 0802. 28 In these cohorts, non-relapse mortality could be stratified by AA1 versus AA2 versus AA3, although day 28 CR/PR was not significantly different in patients with mild, Glucksberg grade I-II aGVHD and AA1-2 biomarker grades. CR/PR was also not significantly different between AA2 and AA3 biomarker grades in severe, Glucksberg grade III-IV aGVHD, 28 leaving room for future refinement of the algorithm.…”
Section: Blood Biomarkersmentioning
confidence: 80%
“…28 In these cohorts, non-relapse mortality could be stratified by AA1 versus AA2 versus AA3, although day 28 CR/PR was not significantly different in patients with mild, Glucksberg grade I-II aGVHD and AA1-2 biomarker grades. CR/PR was also not significantly different between AA2 and AA3 biomarker grades in severe, Glucksberg grade III-IV aGVHD, 28 leaving room for future refinement of the algorithm. As with the Minnesota (MN) clinical Risk Score, proteomics-based risk stratification of aGVHD has yet to be tested prospectively.…”
Section: Blood Biomarkersmentioning
confidence: 80%
See 1 more Smart Citation